2020
DOI: 10.3329/bjid.v7i00.50155
|View full text |Cite
|
Sign up to set email alerts
|

Evidences on Irrational Anti-Microbial Prescribing and Consumption among COVID-19 Positive Patients and Possible Mitigation Strategies: A Descriptive Cross Sectional Study

Abstract: Background: Increased antimicrobial consumption has increased the burden on worsening situation of antimicrobial resistance throughout the world. Objective: The purpose of this study was to assess the practice of irrational antibiotic prescribing and consumption among COVID-19 positive patients of Bangladesh and its possible impact on existing AMR. Methodology: This was a cross-sectional study conducted among SARS-CoV-2 positive patients from a tertiary COVID-19 PCR testing center in Dhaka between … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In Bangladesh, during the early months of the pandemic, there were reports of widespread antimicrobial consumption among COVID-19 positive and suspected patients-in most cases even without a prescription from a certified physician. In a previous study conducted among Bangladeshi COVID-19 patients isolating at home with mild or asymptomatic infection, 63% received one or more antimicrobial agents, including investigational drugs such as ivermectin, remdesivir, and favipiravir [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Bangladesh, during the early months of the pandemic, there were reports of widespread antimicrobial consumption among COVID-19 positive and suspected patients-in most cases even without a prescription from a certified physician. In a previous study conducted among Bangladeshi COVID-19 patients isolating at home with mild or asymptomatic infection, 63% received one or more antimicrobial agents, including investigational drugs such as ivermectin, remdesivir, and favipiravir [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is a scarcity of data regarding antimicrobial use among hospital admitted suspected COVID-19 patients in Bangladesh. Available studies reported antibiotic use among confirmed COVID-19 patients, suggesting a wide range of antibiotic use during the COVID-19 pandemic [ 35 , 36 ]. Considering the scarcity of antimicrobial data in this overstressing COVID-19 pandemic situation in Bangladesh, we assessed the proportion of antimicrobial use and factors associated with antibiotic use among suspected COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…75 Broad-spectrum antimicrobial agents are prescribed at high rates to combat bacterial and fungal coinfection. 75 Azithromycin, ivermectin, and doxycycline were the most frequently used antibiotics in Bangladesh 76 and worldwide. 77 Methylation mediated by methylases encoded by erm genes (especially ermA and ermB) are responsible for Azithromycin 78 Overall, this approach provides valuable insights on the composition of the respiratory microbiome from both vaccinated and nonvaccinated patients and picturizes its relationship with coinfections and/or other organisms that may have a significant impact on SARS-CoV-2 disease progression and prognosis.…”
Section: Discussionmentioning
confidence: 99%